2015
DOI: 10.1590/0004-282x20140180
|View full text |Cite
|
Sign up to set email alerts
|

Placebo and nocebo effects in the neurological practice

Abstract: Knowledge of placebo and nocebo effects is essential to identify their influence on the results in clinical practice and clinical trials, and thereby properly interpret their results. It is known that the gold standard of clinical trials research is the double-blind, placebo-controlled, randomized clinical study. The objective of this review is to distinguish specific from non-specific effects, so that the presence of positive effects in the group that received placebo (placebo effect) and the presence of adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…Indeed, perhaps non-immune causes of neuronal destruction are sufficient to release immunogenic Kv1 antigens and provoke autoantibody production. 16 22 26 Interestingly, the immunotherapy response observed in 27% of patients is very similar to the placebo response rates observed in several other neurological diseases, 37 and much lower than those reported in LGI1 or CASPR2 antibody-associated syndromes. 7–9 11 15 29 35 However, conclusions regarding treatment outcomes are only definitive after blinded interventional studies.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, perhaps non-immune causes of neuronal destruction are sufficient to release immunogenic Kv1 antigens and provoke autoantibody production. 16 22 26 Interestingly, the immunotherapy response observed in 27% of patients is very similar to the placebo response rates observed in several other neurological diseases, 37 and much lower than those reported in LGI1 or CASPR2 antibody-associated syndromes. 7–9 11 15 29 35 However, conclusions regarding treatment outcomes are only definitive after blinded interventional studies.…”
Section: Discussionsupporting
confidence: 75%
“…In marked contrast, patients with double-negative VGKC antibodies respond poorly to immunotherapy, with response rates equal to those of placebo studies, or to rates observed from patients with negative VGKC test results. 26 28 44…”
Section: Features Associated With Double-negative Vgkc Antibodiesmentioning
confidence: 99%
“…The conditioning mechanism is evident when the patient experienced negative results with previous other drugs. [ 9 ]…”
Section: What It Means In Clinical Practice?mentioning
confidence: 99%